A comparison study of radiation effective dose in ECG-Gated Coronary CT Angiography and calcium scoring examinations performed with a dual-source CT scanner - Sabarudin, Akmal; Tiong, Wei Siong; Ang, Wee Chin; Ng, Kwan Hoong; Karim, Muhammad Khalis Abdul (Nature Research, 2019)
In this report we have evaluated radiation effective dose received by patients during ECG-gated CCTA examinations based on gender, heart rate, tube voltage protocol and body mass index (BMI). A total of 1,824 patients were retrospectively recruited (1,139 men and 685 women) and they were divided into Group 1 (CCTA with calcium scoring), Group 2 (CCTA without calcium scoring) and Group 3 (only calcium scoring), where the association between gender, heart rate, tube voltage protocol and body mass index (BMI) were analysed. Examinations were performed using a retrospective ECG-gated CCTA protocol and the effective doses were calculated from the dose length product with a conversion coefficient of 0.026 mSv.mGy −1 cm −1 . No significant differences were observed in the mean effective dose between gender in all groups. The mean estimated dose was significantly higher when the heart rate was lower in Group 1 (p < 0.001) and Group 2 (p = 0.002). There were also significant differences between the mean effective dose in tube voltage protocol and BMI among the three groups. The mean effective dose was positively correlated with BMI (p < 0.001), but inversely related to the heart rate. This study supported the theory that a high heart rate, low tube voltage and low BMI could significantly reduce radiation dose exposure. © 2019, The Author(s).